Antiemissive coatings. (October 2015) - Vetrov, N Z; Kostrin, D K; Lisenkov, A A; Popova, M S
Abstract: High demands, the implementation of which determines the quality of the products in whole, are presented to the grid electrodes of the generating lamps as the elements that determine parameters and characteristics of electronic devices. The grid is a complex structure with a certain degree of transparency. The choice of material of the grid electrodes is determined by the conditions of their operation and design features of the device. Grid nodes are located in the area of the electron beam and during operation of a lamp they should have high heat dissipation to maintain their geometric characteristics and possess a low coefficient of secondary emission.